In Oleic Acid-Induced ARDS, Effects of Tocilizumab and Dexamethasone on the Downregulation of Proinflammatory Cytokines and Upregulation of Antioxidants in the lung. - Terzi, Funda; Demirci, Beste; Çınar, İrfan; Alhilal, Mohammad; Erol, Hüseyin Serkan (Research Square Platform LLC, 2022)
Abstract Background Acute respiratory shortage syndrome (ARDS) is a life-threatening disease formed by the induction of inflammatory cytokines and chemokines in the lungs. There is a dearth of drug treatments that can be used to prevent cytokine storms in ARDS treatment. This study aimed to investigate the efficacy of tocilizumab and dexamethasone on oxidative stress, antioxidant parameters, and cytokine storm in acute lung injury caused by oleic acid in rats. MethodsAdult male rats, CN (healthy, n=6), OA (oleic acid, n=6), OA+TCZ-2 (Oleic acid and Tocilizumab 2mg/kg, n=6), OA + TCZ- 4 (Oleic acid and Tocilizumab 4 mg/kg, n=6), and OA+DEX-10 (Oleic acid and Dexamethasone 10mg/kg, n=6) were divided into five groups. All animals were sacrificed for histopathological, immunohistochemical, biochemical, PCR analyses, and SEM imaging.ResultsThe expression of TNF-α, IL-1β, IL-6, and IL-8 cytokines in rats with acute lung injury with oleic acid was downregulated in the TCZ and DEX groups compared to the OA group. (P<0.05). The MDA level in the lung tissue was statistically lower in the OA+TCZ-4 group compared to the OA group. It was determined that SOD, GSH, and CAT levels decreased in the OA group and increased in the TCZ and DEX groups (P<0.05). Histopathological findings such as thickening of the alveoli, hyperemia, and peribronchial cells were found to be similar to the control group in TCZ and DEX group rat lung tissue. With SEM imaging of the lung tissue, it was found that the alveolar lining layer became indistinct in the OA, OA+TCZ-2 and OA+TCZ-4 groups.ConclusionsIn the acute lung injury model caused by oleic acid, tocilizumab and dexamethasone are thought to be effective in preventing cytokine storm by downregulating the expression of proinflammatory cytokines such as TNF-α, IL-1β, IL-6, and IL-8. Against the downregulation of antioxidant parameters such as SOD and GSH in the lung tissue caused by oleic acid, tocilizumab and dexamethasone upregulated and showed a protective effect in cell damage.
Keywords: 3. Good health